Survivability model for reconfigurable service carrying network based on the stochastic Petri net - Liang ZHAO; Hong ZOU; Xiao-hui ZHANG (Tongxin xuebao)
Aiming at the defect that the security attribute of RSCN couldn't be described with measurement,a survivabil-ity model for RSCN was proposed based on the stochastic Petri net.Firstly,a non-Markovian stochastic Petri net for RSCN was proposed,and then the state schematics was educed based on the FCFS fault repair policy subsequently.Fina-ly,the survivability model was concluded based on the probability equation of system state by importing supplementary variable.The model was analyzed and validated for validity through emu ational experiments.The emulational results show that the comparability between the computed-results of model and emulational results is good,and the model can be used to discribe the survivability for RSCN.